Silent information regulator 1 mediates H2S-inhibited chronic restraint stress-induced depressive-like behaviors by regulating hippocampal autophagy. Issue 3 (26th December 2022) - Du, Lv; Chen, Lei; Luo, Bang; Chen, Yong-Jun; Zhang, Ping; Tang, Yi-Yun; Jiang, Jia-Mei; Zou, Wei
Abstract : Objectives: Our previous study has demonstrated that hydrogen sulfide (H2 S), a novel gasotransmitter, attenuates excessive autophagy and depressive-like behaviors in chronic restraint stress (CRS)-exposed rats, but the underlying molecular mechanism remains to be elucidated. Silent information regulator 1 (SIRT1), a deacetylase at the consumption of NAD+ plays an important regulatory role in depression. Hence, this study aimed to investigate whether SIRT1 mediates the protective effect of H2 S on CRS-induced depressive-like behaviors by regulating hippocampal autophagy. Methods: Adult male Sprague-Dawley (SD) rats were subjected to CRS (6 h × 28 days) to induce depression-like behavior. Rats were injected with sodium hydrosulfate (NaHS, 100 μmol/kg/d, i.p.), as a donor of H2 S, alone or in combination with Sirtinol (a SIRT1 inhibitor; 10 nmol, i.c.v.) during CRS process. The depression-like characteristics of rats were assessed by the novelty-suppressed feeding test (NSFT), tail suspension test (TST), forced swimming test (FST) and open field test (OFT). The number of hippocampal autophagosomes was detected by transmission electron microscopy. The expressions of hippocampal autophagy-related proteins were measured by western blotting analysis. Results: Sirtinol blocked the inhibitory effect of H2 S on depressive-like behaviors in CRS-exposed rats according to NSFT, TST, FST and OFT. In addition, sirtinol reversed the protective response of H2 S to CRS-induced excessive autophagy, as proved by the increases in the number of autophagosomes and the expression of Beclin-1 as well as a decrease in the expression of P62 in the hippocampus. Conclusion: These results indicated that SIRT1 contributes to the antidepressant-like function of H2 S during CRS via reducing hippocampal autophagy.